2020
DOI: 10.1021/acs.jpca.0c05360
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Study on the Fundamental and Valence Excited States of Dibromine in T, P, and H Clathrate Cages

Abstract: This work evaluates the performance of different DFT models in the accurate prediction of the guest−host intermolecular potentials for the ground and excited states of Br 2 in the tetrakaidecahedral (T), pentakaidecahedral (P), and hexakaidecahedral (H) clathrate cages. Of a set of density functionals, we found that PBE0-D3 and wb97XD provide a physically sound and quantitatively correct description of the interaction and transition energies of low-lying valence excited states of Br 2 inside these clathrate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…In previous work, we choose ω-B97X-D/aVTZ as a consistently good DFA for describing the interaction energy and the spectroscopic behavior of dihalogens inside clathrate cages. 15 In reproducing these smaller complexes, we confirm that its description of interaction energies and PES provides consistent results, albeit not perfect.…”
Section: The Shape Of the Well For The Xb And Hx Complexesmentioning
confidence: 66%
See 2 more Smart Citations
“…In previous work, we choose ω-B97X-D/aVTZ as a consistently good DFA for describing the interaction energy and the spectroscopic behavior of dihalogens inside clathrate cages. 15 In reproducing these smaller complexes, we confirm that its description of interaction energies and PES provides consistent results, albeit not perfect.…”
Section: The Shape Of the Well For The Xb And Hx Complexesmentioning
confidence: 66%
“…More recently, we have analyzed the performance of different DFA in describing this singular interaction aiming to study the spectroscopic properties of crystalline halogen hydrates systems beyond the single clathrate cage. Our first attempt was not very encouraging; however, a more detailed study suggested a couple of functionals as promising candidates for predicting the UV–vis transitions using the time‐dependent DFT 15 . However, since the correct description of the hydrate requires not only an accurate prediction of the vertical transitions but also the interaction with the cages and the dynamics of the guest inside, we were interested in confirming if, as the saying goes, we were getting the correct answer for the right reason.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation